Cultural and Religious Practices Over Evidence-Based Science in deciding the range of assisted reproductive technology offered - Rashid, Fahmida; Siddiqui, Maruf; Sattar, MA; Begum, Rashida (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Background: Infertility affects approximately one in eight couples globally and is influenced by medical, sociocultural, and religious factors. Assisted reproductive technology (ART) offers hope to individuals facing infertility, yet cultural and religious norms significantly affect its accessibility, acceptance, and utilization worldwide. Objective: To explore the impact of cultural and religious practices on the acceptance and application of evidence-based ART. Methods: This narrative review analyzes recent literature; relevant published reviews on the topic were searched on PubMed, Google Scholar, Medline, and the Cochrane Library on ART usage patterns across diverse cultural and religious contexts. It examines the interplay between theological doctrines, ethical considerations, and societal norms in ART decision-making. Data from global studies support the findings. Results: Cultural and religious beliefs dictate ART accessibility, with pronounced disparities between secular and theocratic regions. While Shi’a Islam, Hinduism, Buddhism, and Judaism demonstrate high acceptance levels for ART, Catholicism and Orthodox Christianity exhibit restrictive stances. These constraints lead to cross-border infertility tourism, where patients seek treatments unavailable in their home countries. Additionally, in settings like Bangladesh, financial and societal pressures amplify ART inaccessibility. Conclusions: Cultural and religious frameworks significantly shape ART policies and practices. Bridging the gap between these frameworks and evidence-based science requires collaborative efforts among stakeholders, including medical professionals, religious leaders, and policymakers, to ensure equitable access to ART. J Bangladesh Coll Phys Surg 2025; 43: 173-177